Acousto-Optics and Photoacoustics (AOPA) Conference of COO-SPIE Congress - Śliwiński, Antoni (Archives of Acoustics, 2006)
Warsaw, 28 August - 2 September, 2005 The AOPA (Acousto-Optics and Photo-Acoustics) conference was one of the 14 topical conferences consisting of the International Congress of SPIE (The International Society for Optical Engineering) on Optics and Optoelectronics organised by SPIE Polish Chapter, SPIE Europe and the Warsaw University of Technology. It was concerned with physical and technological aspects of light and sound interactions (acousto-optics, AO) as well as with problems of sound generation by light (photo-acoustics and its spectroscopy, PAS) and applications of the both domains in physics, technology, biology, medicine, chemistry and other branches of contemporary knowledge. Up the whole 34 papers were presented in which 12 invited, 16 oral and 8 poster presentations. Finally, 30 papers have been accepted for publication in SPIE Proceedings (see below). The conference had 7 oral sessions and 1 poster session.